2010
DOI: 10.1063/1.3494539
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moment surface of the van der Waals complex CH4–N2

Abstract: The interaction-induced dipole moment surface of the van der Waals CH(4)-N(2) complex has been calculated for a broad range of intermolecular separations R and configurations in the approximation of the rigid interacting molecules at the MP2 and CCSD(T) levels of theory using the correlation-consistent aug-cc-pVTZ basis set with the basis set superposition error correction. The simple model to account for the exchange effects in the range of small overlap of the electron shells of interacting molecules and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
12
0
2
Order By: Relevance
“…El-Kader et al [76] determined the contributions of multipolar polarizabilities to the isotropic and anisotropic light scattering induced by intermolecular interactions in gaseous CH 4 . Zvereva-Loëte et al [77] and Buldakov et al [78] reported an extensive study on the dipole moment surface and dipole polarizability surface for the CH 4 -N 2 complex, a system of importance for the atmospheric physics of Titan. The calculation of the interaction-induced dipole moment, polarizability, and first and second hyperpolarizability of the H 2 O-Rg (Rg ¼ He, Ne, Ar, Kr and Xe) complexes was reported by Haskopoulos and Maroulis [79].…”
Section: Interaction-induced Electric Propertiesmentioning
confidence: 98%
“…El-Kader et al [76] determined the contributions of multipolar polarizabilities to the isotropic and anisotropic light scattering induced by intermolecular interactions in gaseous CH 4 . Zvereva-Loëte et al [77] and Buldakov et al [78] reported an extensive study on the dipole moment surface and dipole polarizability surface for the CH 4 -N 2 complex, a system of importance for the atmospheric physics of Titan. The calculation of the interaction-induced dipole moment, polarizability, and first and second hyperpolarizability of the H 2 O-Rg (Rg ¼ He, Ne, Ar, Kr and Xe) complexes was reported by Haskopoulos and Maroulis [79].…”
Section: Interaction-induced Electric Propertiesmentioning
confidence: 98%
“…(6) was obtained in "constant-ratio" approximation. 59,60 Parameters needed for computation of multipolar expansion series are evaluated at the CCSD(T)/aug-cc-pVQZ level of theory within finite-field approach 61 and reported in Table II. For coefficient C 0 6 , we compute a value of 151.93 E h a 6 0 using the CCSD propagator method 62 in aug-cc-pVQZ basis set.…”
Section: Asymptotic Behaviormentioning
confidence: 99%
“…In the framework of the long-range approximation [36], the multipolar expansion applied successfully in several studies [37,38,39], was used to generate points on the PES. Thus the potential energy may be expressed as…”
Section: Page 5 Of 18mentioning
confidence: 99%